Clinical and molecular analysis of Noonan syndrome in Indonesia: a case report - Iffa Mutmainah; Willy Nillesen; Farmaditya Mundhofir; Tri Winarni; Ineke van der Burgt; Helger Yntema; Sultana Faradz (Indonesian Pediatric Society, 2016)
Noonan syndrome (NS; OMIM#163950) is a relatively common autosomal dominant disorder with a worldwide prevalence of approximately 1:1,000 to 1:2,500. The syndrome is characterized by distinctive facial features, congenital heart defects (CHD), and short stature. Distinctive facial features consist of a broad and high forehead, hypertelorism, downslanting palpebral fissures, a high arched palate, low set and posteriorly rotated ears with a thick helix, and a short neck with excess nuchal skin and low posterior hairline. Additional relatively frequent features include chest deformities, cryptorchidism in males, mild intellectual disability, and bleeding diathesis.1,2In 2001, missense mutations in